Deformation of Steel Slag Asphalt Mixtures Under Normal Temperature Water Immersion - Wang, Chao; Zhang, Caili (Frontiers in Materials, 2021)
In order to study the deformation resistance of steel slag asphalt mixture under rainy condition, limestone asphalt mixture and steel slag asphalt mixture were soaked at room temperature for 120 days, and then rutting test and triaxial compression test were carried out respectively. The results show that the deformation resistance of SSAM is improved after 120 days of immersion, the cohesion does not decrease significantly, and the internal friction angle increases by 25.1%; the deformation resistance of LAM decreases significantly, the cohesion decreases by 27.1%, and the internal friction angle decreases by 21.1%. To study the reason for the increase of anti deformation ability, the adhesion test of asphalt and the microscopic study of steel slag surface were carried out respectively. The experimental results show that the cohesion of steel slag does not decrease significantly after immersion, which is due to the excellent adhesion between steel slag and asphalt, and the increase of internal friction angle is due to calcium hydroxide and other crystals formed on the surface of steel slag mixture after immersion, which increases the surface roughness of steel slag aggregate and increase the internal friction angle of steel slag asphalt mixture.The mechanical properties of semi-rigid asphalt pavement are analyzed by ANSYS. It is found that the shear stress of this type of pavement is large, and it is easy to produce permanent deformation. Under the influence of moisture, the anti deformation ability of steel slag asphalt mixture can grow, which is conducive to the high temperature deformation resistance of asphalt pavement. From the test section of two years of operation, the steel slag asphalt mixture pavement has no pavement diseases such as cracking, loosening, rutting,which shows good road performance.